Teachers’ perception on the causes for cheating among primary school children in Misurata, Libya - Abd 'Aziz Abu Bakar Afat,; Kamarulzaman Abdul Ghani , (Faculty of Education, Universiti Kebangsaan Malaysia, 2010)
The aim of this study is to identify teachers’ perception on the most important causes for cheating among primary school children; and to study whether there is a significant difference between the variables: gender, educational qualifications and years of experience. The sample size is 174 teachers. The questionnaire employed in this study consists of 19 items categorized into three causes related to family, school and media. The study found that the most important causes related to: family, is the lack of familial guidance and counseling; school, is the absence of disciplinary actions for those who cheat; and media, is the absence of programmes on guidance and counseling. Meanwhile, the statistical data related to media show that there are significant differences by gender in favour of females. Causes related to family show significant differences in academic background. Findings also show significant statistical differences on family’s education background which contributed to cheating. There was also no significant difference for years of experience. This study recommends: the importance of educating families to play its role in preparing children to sit for examination, and reducing the anxiety among students caused by test performance in tests; and encouraging teachers to carry out disciplinary acts towards students who cheat. Failure to carry out these actions would further encourage the phenomenon of students cheating. In addition, the media should broadcast programmes on guidance and counseling. Religious seminars should also be carried out to explain the risks of cheating, reasons why cheating is not permissible, and explaining the values, educational commitment, morale and basic rules in their daily lives. These actions are to achieve excellence in students’ educational performance and activities.